Εξοικονόμηση ενέργειας σε σιδηροδρομικό δίκτυο συνεχούς ρεύματος με τη χρήση υπερπυκνωτών - Γούλας, Θεόδωρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Ηλεκτρικής Ισχύος, 2017)
This diploma thesis analyzes the introduction of energy storage systems in an urban metro network, which deploy the regenerative braking energy of a railway vehicle. The main purpose is to optimize the energy efficiency of the system and improve voltage stability of the whole network. Initially, the installation method of energy storage systems will be analyzed in the existing network. Then, a comparative analysis will be conducted upon the available energy storage technologies, so as to determine the most efficient one, in terms of the special features of a typical urban metro system. Afterwards, a power flow control algorithm of the energy storage system will be proposed. The energy storage system will be modelled in Matlab/Simulink in order to examine the correctness of the proposed algorithm. This will be achieved by comparing Matlab/Simulink simulation results with the respective results of an actual energy storage system, by utilizing the Triphase application. In order to verify the energy efficiency of the proposed algorithm a specific part of a typical urban railway system will be developed in Matlab/Simulink and then the simulation results will be elaborately examined. Finally, several scenarios will be examined, to validate further the experimental results. Specifically, the effect of number, capacity, and position of energy storage systems, as well as the traffic conditions of the metro network will be investigated, so as to conclude to the optimal combination of these parameters.